2017
DOI: 10.1002/pros.23401
|View full text |Cite
|
Sign up to set email alerts
|

A urinary biomarker‐based risk score correlates with multiparametric MRI for prostate cancer detection

Abstract: The novel urinary biomarker-based SelectMDx score is a promising tool in PCa detection. This study showed promising results regarding the correlation between the SelectMDx score and mpMRI outcomes, outperforming PCA3. Our results suggest that this risk score could guide clinicians in identifying patients at risk for significant PCa and selecting patients for further radiological diagnostics to reduce unnecessary procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 21 publications
(36 reference statements)
2
65
0
3
Order By: Relevance
“…). The SelectMDx score was also associated with multiparametric magnetic resonance imaging outcomes and outperformed the PCA3 test …”
Section: Ergmentioning
confidence: 99%
“…). The SelectMDx score was also associated with multiparametric magnetic resonance imaging outcomes and outperformed the PCA3 test …”
Section: Ergmentioning
confidence: 99%
“…Thus, the authors suggested that this urine test could serve as a urine‐based molecular marker of SPCa and be used to triage men with a clinical suspicion of PCa. Similar studies have been reported for other urine‐based markers, such as the one included in the commercially available SelectMDx test . Nevertheless, in the current study tissue‐based mRNA biomarkers were applied with the aim of improving risk stratification of men undergoing SB.…”
Section: Discussionmentioning
confidence: 60%
“…Haese recently reported in systematic sextant biopsies patients that HOXC6 and DLX1 measurements improved the calibration of the model, compared to the clinical risk factors alone. The net benefit of the biomarkers was mainly observed for low-risk situations [15]-a condition shown by Hendricks to be most prevalent in low PI-RADS scores [6]. However, in this series, only a minority was imaged prior to biopsies and none received IGB, thereby questioning the practical value of this observation.…”
Section: Discussionmentioning
confidence: 71%
“…This proprietary model of prediction combines biomarker expressions in prostatic epithelium with clinical risk factors and was recently mentioned in the EAU guidelines to avoid unnecessary biopsies. Hendriks reported a strong correlation with MRIs secondarily performed for persistent clinical suspicion or for cancer staging-a double-edged result as it simultaneously vindicated MDx-2 as a proxy for significant cancer that constitutes the bulk of PI-RADS scores 4 and 5, but also questioned the value that it might have retained in the reverse situation of upfront MRI [6].…”
Section: Introductionmentioning
confidence: 99%